2021
DOI: 10.1103/physrevd.103.074504
|View full text |Cite
|
Sign up to set email alerts
|

Sampling usingSU(N)gauge equivariant flows

Abstract: We develop a flow-based sampling algorithm for SU(N ) lattice gauge theories that is gaugeinvariant by construction. Our key contribution is constructing a class of flows on an SU(N ) variable (or on a U(N ) variable by a simple alternative) that respect matrix conjugation symmetry. We apply this technique to sample distributions of single SU(N ) variables and to construct flow-based samplers for SU(2) and SU(3) lattice gauge theory in two dimensions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 59 publications
(57 reference statements)
0
67
0
Order By: Relevance
“…Furthermore, the masking provides a scheme for efficient sampling and generation of events. More advanced normalizing flow techniques have recently been developed by various researchers for use within physics [35,36,38,49]. Exploration of these models is an interesting and exciting avenue for future work.…”
Section: Normalizing Flowsmentioning
confidence: 99%
“…Furthermore, the masking provides a scheme for efficient sampling and generation of events. More advanced normalizing flow techniques have recently been developed by various researchers for use within physics [35,36,38,49]. Exploration of these models is an interesting and exciting avenue for future work.…”
Section: Normalizing Flowsmentioning
confidence: 99%
“…3 In fact, it is somewhat surprising that autoencoders appear to perform worse on the nominally easier task of a bump hunt in leptons than on the superficially much more complicated task of jet image recognition and classification, since leptons live on a phase space of fixed dimension. The increasing prominence of "physics-inspired neural networks" -where networks with important symmetry principles (such as gauge equivariance and Lorentz symmetry) hard-coded into the network architecture perform better than networks which are forced to learn these principles from scratch [54][55][56] -suggests that knowledge of the topology may in fact be necessary to appropriately interpret the autoencoder performance. We illustrate this point with the low-dimensional examples described above, and speculate on how these principles might be applied in the context of phase space.…”
Section: Jhep04(2021)280mentioning
confidence: 99%
“…It employs multiple layered Artificial Neural Networks to learn higher dimensional correlations in the data. Machine learning and Deep Learning methods have been widely used both in theory [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and in experimental high energy physics [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Previous studies [18,20] on identifying the QCD phase transitions have shown that Convolutional Neural Network (CNN) based models can accurately classify the underlying equation of state from a hydrodynamic evolution using the p tφ spectra of pions (differential transverse and angular distributions in the transverse plane).…”
Section: Pointnet For Classifying the Eosmentioning
confidence: 99%